2005
DOI: 10.1097/01.brs.0000164099.92112.29
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the Numeric Pain Rating Scale in Patients with Low Back Pain

Abstract: Clinicians can be confident that a 2-point change on the NPRS represents clinically meaningful change that exceeds the bounds of measurement error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
758
4
21

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,200 publications
(790 citation statements)
references
References 30 publications
7
758
4
21
Order By: Relevance
“…The MCII was determined to be the magnitude of change associated with the upper-left corner of the curve, where both sensitivity and 1 minus specificity are maximized. 4 Area under the ROC curve (AUC) estimates and their associated 95% CIs were also provided. AUC can be interpreted as the probability that a randomly chosen patient score showing major improvement will have a higher score than a randomly chosen patient score showing unimportant change.…”
Section: Discussionmentioning
confidence: 99%
“…The MCII was determined to be the magnitude of change associated with the upper-left corner of the curve, where both sensitivity and 1 minus specificity are maximized. 4 Area under the ROC curve (AUC) estimates and their associated 95% CIs were also provided. AUC can be interpreted as the probability that a randomly chosen patient score showing major improvement will have a higher score than a randomly chosen patient score showing unimportant change.…”
Section: Discussionmentioning
confidence: 99%
“…The primary study parameter was pain reduction [NRS (Breivik et al., 2000; Grotle et al., 2004; Van der Roer et al., 2006; Farrar et al., 2001; Childs et al., 2005)]. The 0–10 verbal numeric rating scale (NRS‐11) is a tool that enjoys widespread clinical use due to its ease of administration.…”
Section: Methodsmentioning
confidence: 99%
“…Because of those findings, we can only speculate that the higher demand of analgesics in most of those patients might be due to a different reason than ongoing SIJ pain. The patient population in our study showed an average decrease on the VAS of 37 points 24 months after distraction arthrodesis of the SIJ was performed, reaching far beyond the minimum clinically important difference (MCID) [29,30]. Literature reports varying MCID values for the ODI [29,[31][32][33].…”
Section: Discussionmentioning
confidence: 69%